Networked business models in the circular economy - Nogalski, Bogdan (IGI Global, Business Science Reference, 2020)
"This book develops and presents the assumptions of business model in sharing and circular economy as a key determinant of the performance of the company embedded in the network. It also explores the relationship between the business model in sharing and circular economy and achieving company performance in a network environment"-- Provided by publisher.
Keywords: Business networks.; Strategic alliances (Business); Management.; elektronické knihy; electronic books